Association between state Medicaid expansion status and naloxone prescription dispensing. (7th February 2020) - Sohn, Minji; Talbert, Jeffery C.; Delcher, Chris; Hankosky, Emily R.; Lofwall, Michelle R.; Freeman, Patricia R.
Abstract: Objective: To test whether Medicaid expansion is associated with (a) a greater number of naloxone prescriptions dispensed and (b) a higher proportion of naloxone prescriptions paid by Medicaid. Data Sources/Study Setting: We used the IQVIA National Prescription Audit to obtain data on per state per quarter naloxone prescription dispensing for the period 2011‐16. Study Design: In this quasi‐experimental design study, the impact of Medicaid expansion on naloxone prescription dispensing was examined using difference‐in‐difference estimation models. State‐level covariates including pharmacy‐based naloxone laws (standing/protocol orders and direct authority to dispense naloxone), third‐party prescribing laws, opioid analgesic prescribing rates, opioid‐involved overdose death rates, and population size were controlled for in the analysis. Principal Findings: Medicaid expansion was associated with 38 additional naloxone prescriptions dispensed per state per quarter compared to nonexpansion controls, on average ( P = .030). Also, Medicaid expansion resulted in an average increase of 9.86 percent in the share of naloxone prescriptions paid by Medicaid per state per quarter ( P < .001). Conclusions: Our study found that Medicaid expansion increased naloxone availability. This finding suggests that it will be important to consider naloxone access when making federal‐ and state‐level decisions affecting Medicaid coverage.